Linkage of environmental factors and health using a tool: “popular epidemiology” and its applications - Wiwatanadate, Phongtape (Biomedical Sciences and Clinical Medicine, 2024)
The effects of factories and waste dumping sites on community health are usually difficult to prove, requiring expertise and expensive laboratories to investigate. To address this problem, the author has developed an easy to use and relatively inexpensive tool, popular epidemiology, that uses a map to locate clusters of people with health problems near environmental risk factors. Case studies in Thailand demonstrate the tool’s applicability and effectiveness. The popular epidemiology tool developed here enables communities to assess the health effects of environmental risk factors themselves.